LITERATURE REVIEW DETERMINASI OF WORK PRODUCTIVITY AND PERFORMANCE: ANALYSIS OF MOTIVATION AND LEADERSHIP STYLE - Dhika Rinaldy Juniandana (Dinasti International Journal of Education Management And Social Science, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of Work Productivity and Performance: Analysis of Motivation and Leadership Style, A Study of the Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) Motivation has an effect on Work Productivity; 2) Leadership Style has an effect on Work Productivity; 3) Motivation has an effect on performance; 4) Leadership Style has an effect on Performance; and 5) Work Productivity has an effect on Performance.